2019
DOI: 10.1590/1678-4499.20190082
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of white oats cultivated under fertigation with treated sewage effluent and definition of critical limits of Normalized Difference Vegetation Index

Abstract: maximum leaf area index (LAI), panicles per square meter, number of grains per panicle, grain mass, grain yield (GY), and biomass yield (BY). In order to define the NDVI critical limits, NDVI values were generated as a function of relative BY in four phenological stages; NDVI values at 90% and 110% of relative BY were considered critical. Maximum GY (5.775 kg.ha-1) and BY (20,731 kg.ha-1) of white oats were achieved with TSE-induced nitrogen rates of 45 kg.ha-1 and 88 kg.ha-1 , respectively. NDVI readings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The lower growth and yield of white oat in 2018, in relation to agricultural years with milder temperatures, can be compared to results by Coelho et al (2019). These authors evaluated the agronomic performance of white oat in an area close to that of the present study, with the same soil type, in a crop year with milder temperatures (2017).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…The lower growth and yield of white oat in 2018, in relation to agricultural years with milder temperatures, can be compared to results by Coelho et al (2019). These authors evaluated the agronomic performance of white oat in an area close to that of the present study, with the same soil type, in a crop year with milder temperatures (2017).…”
Section: Resultsmentioning
confidence: 82%
“…Similarities in grain and biomass yield among the treatments may be justified by the low response of white oat to N fertilization in irrigated and high fertility conditions (Coelho et al 2019). In a place near the study area, Coelho et al (2019) found no significant differences for white oat biomass Nitrogen fertilization management in white oat using spectral indices yield when rates between 10 and 95 kg ha -1 of N were applied. The authors also noticed that the highest averages for grain yield were observed at a topdressing N rate of 29 kg ha -1 , hence this crop has a low response to N fertilization in high-fertility soils.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The GreenSeeker ® , an active spectral sensor, is an instrument that provides the normalized difference vegetation index (NDVI) via reflectance measurements, this sensor automatically generates NDVI readings from the spectral response of the red bands (650 nm) and nera-infrared (770 nm) (COELHO et al, 2019).…”
Section: Introductionmentioning
confidence: 99%